Commentary: Recognizing our similarities and celebrating our differences – parenting across cultures as a lens toward social justice and equity. (7th March 2022) - Cabrera, Natasha J.
Abstract : Lansford (2022) has aptly and eloquently reviewed the vast scholarly research on cross‐cultural parenting and concludes that similarities in parenting norms and behaviors across cultures reflect universally adaptive behaviors for children's development. Culture‐specific differences are due largely to environmental constraints and affordances as well as cultural norms for expected behavior. This is an exemplar review that tells a clear story of what we have learned from the decades of research on this topic and lays the foundation for future scholarship. Specially compelling is Lansford's argument that we need to take stock of what we know and conduct more of this type of research because the majority of what we have now is biased and does not represent the parenting practices of an increasingly diverse population. In this commentary, I provide some context for the value and potential pitfalls of cross‐cultural research; discuss the importance of theoretically driven research; discuss the benefits of cross‐cultural research; and conclude with some ideas for future investigations.